THE RELATIONSHIP BETWEEN PERSONAL HYGIENE AND THE INCIDENCE OF PITYRASIS VERSICOLOR - Maulina Fadila Putri (PT. Radja Intercontinental Publishing, 2026)
Pityriasis versicolor is a superficial fungal infection caused by Malassezia and is commonly found in tropical regions with high temperatures and humidity. Personal hygiene is known to be a factor that plays a role in the occurrence of this disease. This study aims to analyze the relationship between personal hygiene and the incidence of pityriasis versicolor based on the results of various studies that have been conducted. The method used is a literature review by examining scientific articles from various databases such as ProQuest, ScienceDirect, Scopus, PubMed, Cochrane Library, EBSCOhost, ClinicalKey, and Sage Publications. The results of the study showed that all analyzed studies stated a significant relationship between personal hygiene and the incidence of pityriasis versicolor. Individuals with poor personal hygiene have a higher risk of developing pityriasis versicolor compared to individuals who maintain good personal hygiene. Factors such as poor skin hygiene, increased moisture, sebum production, wearing inappropriate clothing, and an unhygienic environment play a role in increasing the growth of Malassezia . Thus, personal hygiene is a modifiable risk factor in the prevention of pityriasis versicolor. Efforts to improve clean and healthy living behavior are very important to reduce the incidence of this disease, especially in high-risk populations.